1. ## equation

I haven't done math in years, I have no idea what I'm doing wrong

this is one of many problems I'm stuck on:

-6 (x +1) + 4 = 16

I disribute the negative 6 to the ()

-6 (-11x) = 66x

66x=12

x= 12/66

Then I don't do that I get:

-6(2x)+4-4=16-4
-12x=12
x=-1

I've been stuck on this one for hours, I went through the tutorials and everything and I still do not understand.

2. Originally Posted by mdudley
I haven't done math in years, I have no idea what I'm doing wrong

this is one of many problems I'm stuck on:

-6 (x +1) + 4 = 16

I disribute the negative 6 to the ()

-6 (-11x) = 66x

66x=12

x= 12/66

Then I don't do that I get:

-6(2x)+4-4=16-4
-12x=12
x=-1

I've been stuck on this one for hours, I went through the tutorials and everything and I still do not understand.
Hello
$-6(x+1)+4=16$

First let us distribute that -6 through to get

$-6x-6+4=16$

now combining the second and third term we get

$-6x-2=16$

adding two to each side we get

$-6x=18$

dividing by six we get

$x=-3$

3. Originally Posted by Mathstud28
Hello
$-6(x+1)+4=16$

First let us distribute that -6 through to get

$-6x-6+4=16$

now combining the second and third term we get

$-6x-2=16$

adding two to each side we get

$-6x=18$

dividing by six we get

$x=-3$
Ok so I take the -6 and distribute to the ()

and get -6x-6+4=16

is that because of the (x+1) = 1x and 1x multiplied by -6 equals -6x?

then
-6x-6+4=16
-6x-2 + 2 = 16 + 2
-6x = 18
-6x divided by -6 is x and 18 divided by -6 is negative 3
x=-3

so I didn't need to multiply at all? when will I know when to mulitply?

4. Originally Posted by mdudley
Ok so I take the -6 and distribute to the ()

and get -6x-6+4=16

is that because of the (x+1) = 1x and 1x multiplied by -6 equals -6x?

then
-6x-6+4=16
-6x-2 + 2 = 16 + 2
-6x = 18
-6x divided by -6 is x and 18 divided by -6 is negative 3
x=-3

so I didn't need to multiply at all? when will I know when to mulitply?
Not quite:

$(x + 1)$ includes TWO terms, and when you distribute anything to something with more than one term you distribute it to all terms, for example, say we wanted to distribute the number 2 to the (x + 1):

$2(x + 1)$

What it means to distribute is to multiply each term in the parentheses by what's on the outside:

$2(x) + 2(1)$

Now we multiply:

$2x + 2$

Using this, you can see why:

$-6(x + 1) = -6(x) + -6(1) = -6x - 6$

There you are.